Larval development of the Caribbean king crab Maguimithrax spinosissimus (Lamarck, 1818), the largest brachyuran in the western Atlantic (Crustacea: Decapoda: Majoidea) - Turini, Tassia [UNESP]; Colavite, Jessica [UNESP]; Bolaños, Juan A.; Hernandez, Jesus Enrique; Baeza, Juan Antonio; Santana, William [UNESP] (Cambridge University Press (CUP), 2021)
The complete larval development of the spider crab Maguimithrax spinosissimus (Lamarck, 1818) is re-described and illustrated in detail from laboratory-reared material the development consisted of the typical pattern reported for the Majoidea, two zoeal stages and one megalopa the complete larval development from hatching to first crab lasted 5-6 days at temperatures that ranged between 24-28 °C. Both zoeal stages of M. spinosissimus exhibited moderate reduction in the number of setae in the maxilla and maxillipeds, from the first to the second zoeal stage, when compared with other closely related species. Maguimithrax spinosissimus can be easily distinguished from other species belonging to the closely related genus Mithrax by the (i) setation of the endopod of the maxillule, maxilla and second maxilliped in both zoeal stages; (ii) setation of the scaphognathite of the maxilla in the first zoeal stage; (iii) setation of the basis of maxilliped I in the second zoeal stage and megalopa; (iv) morphology of the antennule and antenna in the second zoeal stage; and (v) setation of the antennule, coxal endite of maxilla, and exopod of second maxilliped in the megalopa. All these characters support the recent generic status of Maguimithrax within the Mithracidae. Additional morphological details, not available previously, are provided. This study will provide support for conservation strategies in this species.
Keywords: Larval morphology; lecithotrophy; Majoidea; ontogeny